GLABRA2 Directly Suppresses Basic Helix-Loop-Helix Transcription Factor Genes with Diverse Functions in Root Hair Development. Issue 10 (20th October 2015) - Lin, Qing; Ohashi, Yohei; Kato, Mariko; Tsuge, Tomohiko; Gu, Hongya; Qu, Li-Jia; Aoyama, Takashi
Abstract : GLABRA2 targets and suppresses five basic helix-loop-helix transcription factor genes with diverse functions in root hair development during root hair pattern formation of Arabidopsis thaliana . Abstract: The Arabidopsis thaliana GLABRA2 ( GL2 ) gene encodes a transcription factor involved in the cell differentiation of various epidermal tissues. During root hair pattern formation, GL2 suppresses root hair development in non-hair cells, acting as a node between the gene regulatory networks for cell fate determination and cell differentiation. Despite the importance of GL2 function, its molecular basis remains obscure because the GL2 target genes leading to the network for cell differentiation are unknown. We identified five basic helix-loop-helix (bHLH ) transcription factor genes ( ROOT HAIR DEFECTIVE6 [ RHD6 ], RHD6-LIKE1 [ RSL1 ], RSL2, Lj -RHL1-LIKE1 [ LRL1 ], and LRL2 ) as GL2 direct targets using transcriptional and posttranslational induction systems. Chromatin immunoprecipitation analysis confirmed GL2 binding to upstream regions of these genes in planta. Reporter gene analyses showed that these genes are expressed in various stages of root hair development and are suppressed by GL2 in non-hair cells. GL2 promoter-driven GFP fusions of LRL1 and LRL2, but not those of the other bHLH proteins, conferred root hair development on non-hair cells. These results indicate that GL2 directly suppresses bHLH genes with diverse functions in root hair development.